Learning Strategies Used By High Proficience Students Of SMPN 3 Geger In Developing Speaking Skill; A Case Study - Hesti, Yeni Prima, Prof. Dr. Endang Fauziati, M. Hum, Dra. Siti Zuhriyah Ariatmi, M. Hum (2014)
This study investigates strategies for developing speaking skill: a case study on high proficience students of SMPN 3 GEGER. The purpose of the study is to describe the strategies in improving speaking skill. The type of this research is case study which aims at describing the subjects' learning strategies in improving speaking skill. The subjects of this research are three students chosen based on the speaking class. The data of this research are elicited interview, observation and documentation. The result of this research shows that the three of the subjects uses almost all of the learning strategies proposed by O'Malley and Chamot. However their action and attention in learning speaking are different. S1 uses 12 learning strategies which consists of 5 metacognitive strategies; advance organizer, directive attention, selective attention, self-management, self-evaluation, 5 cognitive strategies which consists of repetition, resourcing, imagery, ealboration, and note taking, and one socio-affective strategy that is question for clarification. S2 uses 11 learning strategies which consists of 5 metacognitive strategies which consists of repetition, resourcing, directed attention, selective attention, selfmanagement, self monitoring, note taking, and self evaluation. S3 uses 7 learning strategies which consists of 3 metacognitive strategies; advance organizer, selective attention, self management, 4 cognitive strategies which consists of repetition, resourcing, and two socio affective strategies which consists of repetition, resourcing, and two socio affective strategies those are cooperation and question for clarification. Based on the result of this research, the researcher concludes that all of the learning strategies used by the subjects are effective strategies which are important to improve the learners' speaking skill. Some learning strategies which are important to improve the learners' speaking skill are: advance organizer, selective attention, self management, repetition, resourcing, and elaboration.